2008
DOI: 10.1021/jf072960b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing Conditions on Acrylamide Content in Black Ripe Olives

Abstract: The presence of acrylamide was investigated in different presentations of commercial black ripe olives, a well-known sterilized alkali-treated product. The analysis was performed by gas chromatography-mass spectrometry (GC-MS) after bromination of acrylamide, using (13C3)acrylamide as internal standard. In-house validation data for commercial ripe olives showed good precision and accuracy of the method, with repeatability below 3% and recoveries between 94 and 105%. Acrylamide was detected in all samples, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(114 citation statements)
references
References 21 publications
4
106
2
2
Order By: Relevance
“…In the present study only the water-soluble phenolic compounds were used, consisting mainly of the dialdehydic form of tyrosol and hydroxytyrosol (Table 3). The above action of dialdehydic form of phenolic compounds might explain the formation of acrylamide in sterilised black olives reported by Casado and Montaño (2008). It has been suggested that another -unknown -mechanism of acrylamide formation must be acting in the table olives, where acrylamide was formed, although free amino acids and reducing sugars were found in small amounts.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the present study only the water-soluble phenolic compounds were used, consisting mainly of the dialdehydic form of tyrosol and hydroxytyrosol (Table 3). The above action of dialdehydic form of phenolic compounds might explain the formation of acrylamide in sterilised black olives reported by Casado and Montaño (2008). It has been suggested that another -unknown -mechanism of acrylamide formation must be acting in the table olives, where acrylamide was formed, although free amino acids and reducing sugars were found in small amounts.…”
Section: Resultsmentioning
confidence: 90%
“…The small amounts of free amino acids and reducing sugars found in olives before sterilisation did not significantly correlate with the acrylamide formed. Therefore, another -unknown -mechanism of acrylamide formation in the case of sterilised table olives was suggested (Casado & Montaño, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, experiments were carried out to evaluate whether the postulated AA inhibitors could effectively reduce AA formation in fried potato strips, which have been reported to be among the principal dietary sources of AA (Friedman, 2003;Tareke, Rydberg, Karlsson, Eriksson, & Tornqvist, 2002). Considering the fact that samples from fried potato strips likely have much more complex chemical profiles than have those from model systems, AA in the defatted extracts was derivatized to 2-bromopropenamide and qualitative and quantitative analyses were accomplished by GC-MS, using isotope-labelled AA as an internal standard (Andrawes, Greenhouse, & Draney, 1987;Casado & Montano, 2008;Zhang et al, 2006). In agreement with previous studies (Zhang et al, 2006;Zhu et al, 2008), this method was robust, reproducible (RSD, 6.8%) and highly sensitive (LOD, 0.015 lg/l).…”
Section: Effects Of Hydrocolloids On Acrylamide Formation In Fried Pomentioning
confidence: 99%
“…The combined extract was concentrated to 1 ml on a rotary evaporator at 45°C under vacuum. The concentrated samples were transferred to Eppendorf tubes and 0.1 ml of triethylamine was added to convert 2,3-dibromopropenamide into 2-bromopropenamide (2-BPA) (Casado & Montano, 2008). The solution was vortex-mixed and centrifuged at 14,000 rpm for 10 min.…”
Section: Effects Of Hydrocolloids On Acrylamide Formation In Fried Pomentioning
confidence: 99%
“…The use of rotary flash driers could give rise to temperatures of 400 • C (possibly more) which could potentially give rise to the formation of acrylamide [11] and polycyclic aromatic hydrocarbons (PAHs), which might give rise to concerns for genotoxicity. However chemical analyses performed with the H40 extract have indicated that the content of these components is very low (<100 and <0.5 ppb respectively), and of little concern in comparison to other dietary sources.…”
Section: Introductionmentioning
confidence: 99%